Alaskan holiday a novel - Macomber, Debbie (New York : Ballantine Books, an imprint of Random House, 2018)
Before beginning her new job as sous chef at one of Seattle's finest restaurants, Josie Stewart takes on a six-month position cooking at a lodge in an Alaskan lake town. It's only temporary -- or so she thinks, as she becomes a valued part of the local community, falling in love with the people who call Klutina Lake home. But one Alaskan man, in particular, stands out among Josie's new friends: Palmer Saxon, a quiet, intense sword craftsman, whose very existence forces her to question whether her heart wants to return to Washington at all -- or make Alaska her home.
106874
Keywords: Man-woman relationships; Cooks; Swordsmiths -- United States; Romance/Contemporary.; Contemporary Women; Christmas; Armorers; Women cooks; Love stories; Christmas fiction; Christmas fiction; Romance fiction